Analysis of The Hadith That Women are Created from The Ribs: Theological Issues of Islamic Feminism - Hulisan, Muhammad Fasih (Journal of Feminism and Gender Studies, 2024)
One of the theological issues in Islam is the concept of human creation. Within the scope of the issue of human creation, there is also a discussion of the origin of the creation of women in the hadith. The Hadith about women being created from a rib is one of the theological issues in the issue of Islamic feminism. Therefore, this research is intended to find the location of problems related to the understanding of the hadith, then offer a new view in parsing the theological problems of Islamic feminism and try to produce a reconstruction of understanding of the hadith about women created from ribs. This research uses a qualitative method with a type of library research, accompanied by a hadith criticism approach. This research reveals that the wording of the hadith "women were created from ribs" is more accurately interpreted as a figurative meaning (majazi). So that the reconstruction of the meaning of the hadith leads to a positive connotation and avoids misogynism. Furthermore, the implicit wisdom of the hadith shows that there is a prophetic treatise that leads to education for women to be intensified, as Fethullah Gülen's view in interpreting the hadith.